2022
DOI: 10.3389/fcvm.2022.777946
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Prognostic Model to Predict High-Risk Patients for Coronary Heart Disease in Snorers With Uncontrolled Hypertension

Abstract: PurposeSnoring or obstructive sleep apnea, with or without uncontrolled hypertension, is common and significantly increases the risk of coronary heart disease (CHD). The aim of this study was to develop and validate a prognostic model to predict and identify high-risk patients for CHD among snorers with uncontrolled hypertension.MethodsRecords from 1,822 snorers with uncontrolled hypertension were randomly divided into a training set (n = 1,275, 70%) and validation set (n = 547, 30%). Predictors for CHD were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In addition, the ROC curve analysis of this study showed that the diagnostic value of non-calcified plaque volume and loading for the recurrence of adverse cardiovascular events within 1 year in unstable CHD patients was comparable to that of carotid intima-media thickness, LVEF, hypertension, and so on. The carotid intima-media thickness, LVEF, and hypertension have been confirmed to be good predictors of adverse cardiovascular events (17)(18)(19)(20), which indicates that the use of CCTA to measure the volume and loading of non-calcified plaques is of good value in diagnosing adverse cardiovascular events that recur within 1 year in patients with unstable CHD.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, the ROC curve analysis of this study showed that the diagnostic value of non-calcified plaque volume and loading for the recurrence of adverse cardiovascular events within 1 year in unstable CHD patients was comparable to that of carotid intima-media thickness, LVEF, hypertension, and so on. The carotid intima-media thickness, LVEF, and hypertension have been confirmed to be good predictors of adverse cardiovascular events (17)(18)(19)(20), which indicates that the use of CCTA to measure the volume and loading of non-calcified plaques is of good value in diagnosing adverse cardiovascular events that recur within 1 year in patients with unstable CHD.…”
Section: Discussionmentioning
confidence: 91%
“…Our previous studies have demonstrated that WC is an important risk factor for CHD in snorers with uncontrolled hypertension. 27 We think that this is because WC is a better indicator of abdominal obesity in snorers than BMI. Epidemiological data show that snorers have increased abdominal obesity 1 and WC is positively associated with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome was CHD that occurred during follow-up, including hospitalized angina, myocardial infarction, coronary revascularization and coronary death. 27 …”
Section: Methodsmentioning
confidence: 99%
“…The initial step toward this goal is to identify the risk factors related to cardiovascular complications. Previous studies have demonstrated that cardiovascular complications may arise from multiple factors, including demographic and disease characteristics: age [ 7 ], sex [ 8 ], age of onset [ 9 ] and blood pressure [ 10 ]. Additionally, ultrasonography findings and several laboratory test results may also be factors correlated with cardiovascular complications and include uric acid [ 11 ], pro-brain (B-type) natriuretic peptide [ 7 ], serum lipid [ 8 ], homocysteine [ 12 ], and interventricular septum thickness [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that cardiovascular complications may arise from multiple factors, including demographic and disease characteristics: age [ 7 ], sex [ 8 ], age of onset [ 9 ] and blood pressure [ 10 ]. Additionally, ultrasonography findings and several laboratory test results may also be factors correlated with cardiovascular complications and include uric acid [ 11 ], pro-brain (B-type) natriuretic peptide [ 7 ], serum lipid [ 8 ], homocysteine [ 12 ], and interventricular septum thickness [ 13 ]. Furthermore, anxiety and depression [ 14 , 15 ], diet [ 16 ], smoking, and drinking [ 17 , 18 ] may also contribute to the occurrence of cardiovascular complications.…”
Section: Introductionmentioning
confidence: 99%